Islamic Education in Forming Students' Characters at As-Shofa Islamic High School, Pekanbaru Riau - Eniwati Khaidir; Fitriah M. Suud (Universitas Muhammadiyah Yogyakarta, 2020)
As an effort to form humans, education must have a good and strong foundation because, with this foundation, the direction of the implementation of education is not merely a momentary shock or turmoil. The foundation of education is essential in the process of advancing education. Thus, the basis of education is a fundamental problem because basic education will determine the style and content of education. In the meantime, its relation to Islamic education, the basis or foundation of Islamic education, is the foundation that forms the basis or principle to stand tall. Therefore, the basis of Islamic education must be considered comprehensively in wading through the next educational steps. Al-Qur'an and Hadith are sources of Islamic law and complete knowledge, covering the whole of human life, both the world and the hereafter. Both of them become an apparent clue for humans and the pace of their lives at all times. Al-Qur'an and Hadith, as a basis for Islamic education as well as a source of shari'a teachings, not only work as a book but also exploration for daily life. Islam is a religion that carries a mission so that people conduct education and teaching.